INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN “SI DUKUN 3 IN 1” DI PROVINSI DKI JAKARTA - Dhany Sukma; Muhamad Shendy Adam Firdaus (Jurnal Media Birokrasi, 2020)
The ideal bureaucracy according to Max Weber, one of which is to create service certainty, but the opposite is true. Residents often have a weak bargaining position when accessing public services. They cannot get a guarantee of certainty, especially in terms of service completion time. In fact, it is not uncommon that procedure and cost uncertainty also occurs. Meanwhile, population administration is the most basic public service. Every event in human life is inseparable from population services. This study aims to elaborate the dynamics of population administration services in DKI Jakarta Province, especially in the case of obtaining birth certiϔicate documents. The theory of innovation in public services is used to analyze cases. Research carried out with a qualitative approach. The ϔindings of this research show that public services in the form of the “Si Shaman 3 in 1” program launched by the Jakarta Population and Civil Registry Ofϔice has been successful enough to be an innovation that beneϔits citizens. Without complicated procedures, residents can immediately get population services integratedwith BPJS Health membership. Keywords: public services, innovation, population and civil registration, bureaucracy